Investigating faunal diversity and abundance in the Marianas midwater - Moyer, Isabel M.; Copeland, Adrienne; Egan, Katharine; Collins, Allen G. (Frontiers in Marine Science, 2025)
The midwater ocean (200 m depth to the seafloor) is the largest biome on the planet, supporting a large percentage of global ocean biomass. Difficulties in midwater exploration constrain knowledge about the organisms and ecology of the critical ecosystems it contains. Pacific Ocean expeditions by NOAA Ocean Exploration explored the faunal distributions of many water column taxa, including continued characterization of a zone of aggregated midwater fauna known as the deep scattering layer (DSL). In 2016, NOAA Ocean Exploration conducted a series of remotely operated vehicle (ROV) dives in and around the Marianas Trench. Four of these dives included midwater transects, ranging in depths from 275 to 4000 m. These were the first midwater explorations conducted in the Marianas region. These dives included a deep dive in the trench (482–4000 m) and one dive centered around a hydrothermal vent cloud (275–408 m). Taxonomic annotations of video footage were used to calculate organismal abundances and Shannon-Weiner diversity indices for each transect, partitioned by depth. Higher diversity and richness levels were found in transects within the deep scattering layer (DSL) than in transects outside of the DSL; however, there was no difference in abundance between transects within, above, and below the DSL. Lower levels of diversity were found inside a hydrothermal vent cloud versus outside. This novel exploration furthers current understanding of the diversity and abundance of deep-ocean species in the Marianas region, provides a baseline for faunal distribution trends that can be referenced in future exploration, and enables predictions of midwater ecosystem diversity in global deep-sea trench environments.